Postmodernizm jako kryzys mentalny - Igoriewicz, Tiupa Walerij (Przestrzenie Teorii, 2020)
The article is devoted to the crisis situation of postmodernism. The author assumes that the crisis of postmodernism is a historical process phenomenon and therefore inevitable. The postmodernism of the last decades of the 20th century is presented as most probably the last crisis of the post-rhetoric formation in its culture-creating productivity. The author believes that the recessive reconstruction of the dominant role of authority’s discourse with its imperative, legislative and regulatory competencies, or neo-rhetorical breakthrough of the convergent mentality leading to the domination in people’s spiritual lives as more or less likely scenarios for the further development of the historical situation together with the surging globalism of the human civilization may prove to be universally significant. Moreover, the author focuses on the media tools used to carry out each discursive formation. Those tools open up unique possibilities for executing the neo-rhetorical impulse towards the universal solidarization of life.